2007
DOI: 10.1038/sj.onc.1210307
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of polypyrimidine tract-binding protein suppresses ovarian tumor cell growth and invasiveness in vitro

Abstract: Polypyrimidine tract-binding protein (PTB) is an RNAbinding protein with multiple functions in the regulation of RNA processing and IRES-mediated translation. We report here overexpression of PTB in a majority of epithelial ovarian tumors revealed by immunoblotting and tissue microarray (TMA) staining. By western blotting, we found that PTB was overexpressed in 17 out of 19 ovarian tumor specimens compared to their matchednormal tissues. By TMA staining, we found PTB expression in 38 out of 44 ovarian cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
144
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(162 citation statements)
references
References 28 publications
14
144
3
1
Order By: Relevance
“…These studies have provided meaningful insights into the function of this versatile and ubiquitous protein. Recent studies have shown a role for PTB in ovarian cancer, suggesting that PTB could be a good potential therapeutic target [101]. These structures could, therefore, facilitate the design of a drug against this cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have provided meaningful insights into the function of this versatile and ubiquitous protein. Recent studies have shown a role for PTB in ovarian cancer, suggesting that PTB could be a good potential therapeutic target [101]. These structures could, therefore, facilitate the design of a drug against this cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the components of translational machinery, RNA-binding proteins are also aberrantly expressed in tumors, including PTB (He et al, 2007), HuR (Lopez de Silanes et al, 2003), KH domain-containing protein, and hnRNPD among others (Gouble et al, 2002), with a direct correlation between abnormal expression of a particular RNA-binding protein and tumor formation (CRD-BP) in breast tissue (Tessier et al, 2004). Furthermore, many RNA-binding proteins have been reported to be direct targets of Akt, including YB-1 (Evdokimova et al, 2006), the tumor suppressor Pdcd4 (Palamarchuk et al, 2005), BRF1 (Benjamin et al, 2006) and KSRP (Gherzi et al, 2006), thus linking the Akt pathway to mRNA silencing, degradation, apoptosis and the Wnt signaling pathway through the promotion of the stabilization of b-catenin mRNA, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In ovarian cancer, PTBP1 levels correlate with the degree of malignancy (9). Higher amounts of PTBP1 occur in advanced, as compared with benign, ovarian tumors, and PTBP1 increases when ovarian epithelial cells are immortalized (9). Removal of PTBP1 from ovarian tumor cells makes cell less proliferated, anchorage-independent growth, and cell invasion.…”
Section: Introductionmentioning
confidence: 99%
“…PTBP1 also has multiple functions other than pre-mRNA splicing and affects glioma cell invasion (7). In ovarian cancer, PTBP1 levels correlate with the degree of malignancy (9). Higher amounts of PTBP1 occur in advanced, as compared with benign, ovarian tumors, and PTBP1 increases when ovarian epithelial cells are immortalized (9).…”
Section: Introductionmentioning
confidence: 99%